Digital patterns of media consumption and perception of AI technologies: Habits and expectations of digital audiences - Blaži, Jelena; Žigo, Iva Rosanda; Vidačić, Tomislav (Technium Social Sciences Journal, 2025)
In the context of the accelerated development of artificial intelligence, this paper analyzes the use of traditional and new media, as well as the perceptual changes brought about by the technological environment and changes in the way citizens are informed. The habits and changes of the digital audience and their media preferences are analyzed on the basis of the conducted survey. Caution was also observed regarding the influence of technology, as well as awareness of the transformative potential of artificial intelligence in the information sphere. By combining quantitative and qualitative methods, the work contributes to the understanding of the contemporary media landscape and its interactions with artificial intelligence. The findings indicate differentiated patterns of behavior and the need for a critical evaluation of the impact of AI on media literacy and perception of reality.